Quail Meat Under Threat: Hidden Microplastics Pose Risks to Public Health and Environment - Doğan, Veysel; Salum, Çağatay; Gökmen, Sedat; Atar, Mehmet Sait (Kastamonu Üniversitesi Veteriner Fakültesi, 2024)
Aim to study: This study aimed to determine the presence of microplastics in tissues and organs of quails (Coturnix coturnix) and to evaluate the potential risks of microplastic contamination in terms of human consumption and environmental impacts. Materials and Methods: Organ and tissue samples were analyzed from five laying quails that had died naturally. Samples were treated with 10% KOH and filtered in a laminar flow cabinet. Microplastics were identified using light microscopy and FTIR spectroscopy. Statistical analyses were conducted using SPSS at a significance level of p ≤ 0.05. Results: Microplastics in filament, fragment, and film forms were detected in quail tissues and digestive system contents. Polyethylene and polyvinyl stearate polymers were the most common types of microplastics. The highest microplastic density was found in intestinal contents. The presence of microplastics in edible tissues (breast and leg meat) was identified, posing potential risks for human consumption. Conclusion: The presence of microplastics in quail meat and tissues poses potential risks for human consumption and highlights the prevalence of environmental pollution.
Keywords: Environmental Pollution; Microplastic Contamination; Microplastic; Public Health; Quail; Veterinary Sciences (Other); Veteriner Bilimleri (Diğer)